How Should We Study District Judge Decision-Making? - Pauline T. Kim; Margo Schlanger; Christina L. Boyd; Andrew D. Martin (Washington University Journal of Law & Policy, 2009)
Part I of this Essay describes in detail the institutional setting in which district judges function and how their role differs substantially from that of appellate judges. Part II critiques the existing empirical literature’s predominant method for studying district courts—analysis of district court opinions, usually published opinions—and discuss the limitations and biases inherent in this approach. Part III then proposes a new approach to studying decision-making by district judges.
Keywords: Judicial process; Appeals (Law); Legal research methodology; Judicial decision-making